PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSET (ROA) TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA BANK BUMN PERIODE 2012-2016) - Aisyah Ratnasari (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The value of company is perception investor about level success of company in managing resources in the current year Which are reflected in share prices years before. The value of company Can be seen with the ratio Price Book to Value (PBV). This ratio illustrates how much the market appreciates the value of share books in the company. The purpose of this research is to analyze the influence of Debt to Equity Ratio (DER) dan Return On Asset (ROA) against the Value of company case study on the bank BUMN period 2010-2016.This method research using the associative method Namely connect one variable with other variables. The techniques analysis of the data using correlation, regression, the test t ( partial ) and test f ( simultaneous ). The results of the analysis of reckoning test t shows Debt to Equity Ratio (DER) against the value of company Influential negative and significant with the results -2,154 with significantly 0,045. return On Asset (ROA) against the value of company have influence positive and significant with the result test t 3,307 with significantly 0,004. While for the calculating the test F between DER dan ROA on Simultaneously against the value of company There is a significant influence the 5,663 with the figures significant 0,013. For a company that wants to increase the Company Value it must reduce DER, As more debt may lower the Company's Value. This study also showed a positive number of ROA against the value of company, The bigger the ROA the higher the value of company. Keywords : Debt to Equity Ratio (DER), Return On Asset (ROA), and the value of company.